2018
DOI: 10.1111/jems.12292
|View full text |Cite
|
Sign up to set email alerts
|

Points mechanisms and rewards programs

Abstract: I study points programs, such as frequent flyer and other rewards programs, as a revenue management tool. I develop a two‐period contracting model where a capacity‐constrained firm faces consumers who privately learn their valuations over time. The firm cannot commit to long‐term contracts, but it can commit to allocate any unsold capacity through a points program. This points scheme creates an endogenous and type‐dependent outside option for consumers, which generates novel incentives in the firm's pricing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Keh and Lee [26] found that the level of consumer satisfaction is a predictor of the effect of such programs on brand loyalty and Koo et al [27] demonstrated that the perceived value of a loyalty program is crucial to its effectiveness. Likewise, Temnyalov [28] showed that rewards programs are effective, also, as a strategy for establishing more efficient pricing for sellers.…”
Section: Introductionmentioning
confidence: 99%
“…Keh and Lee [26] found that the level of consumer satisfaction is a predictor of the effect of such programs on brand loyalty and Koo et al [27] demonstrated that the perceived value of a loyalty program is crucial to its effectiveness. Likewise, Temnyalov [28] showed that rewards programs are effective, also, as a strategy for establishing more efficient pricing for sellers.…”
Section: Introductionmentioning
confidence: 99%